Variable expression of the Fragile X Mental Retardation 1 (FMR1) gene in patients with premature ovarian failure syndrome is not dependent on number of (CGG)n triplets in exon 1 - Rehnitz, Julia; Peng, Zhiyu; Zimmer, Jutta; Sinn, Peter; Hagens, Cornelia von; Strowitzki, Thomas; Vogt, Peter H. (Human reproduction, 2011)
AbstractBACKGROUND. Increased expression of the Fragile X Mental Retardation 1 (FMR1) gene in blood cells has been claimed to be associated with variable (CGG)
Gesehen am 31.07.2019